Three years sustained complete remission achieved in a primary refractory ALK-positive anaplastic T large cell lymphoma treated with crizotinib - Carolina Valeria Mahuad; Maria de los Ángeles Vicente Repáraz; Marta E. Zerga; María Florencia Aizpurúa; Claudia Casali; Gonzalo Garate (Rare Tumors, 2016)
The prognosis of the primary refractory anaplastic lymphoma kinase (ALK+) anaplastic T large cell lymphoma is ominous. The identification of molecular targets with potential to drive oncogenesis remains a cornerstone for the designing of new selective cancer therapies. Crizotinib is a selective ATP-competitive inhibitor for ALK, approved for its use in lung cancer with rearrangements on ALK gene. The reported cases describe the use of crizotinib as a bridging strategy prior to allotransplantation; there are no reported prolonged survivals under monotherapy with Crizotinib. We report a case of a primary refractory ALK+ anaplastic largecell lymphoma that sustains complete response after 3 years of crizotinib monotherapy.